1992
DOI: 10.1038/355176a0
|View full text |Cite
|
Sign up to set email alerts
|

Independent binding of the retinoblastoma protein and p107 to the transcription factor E2F

Abstract: The cellular protein p107 and the retinoblastoma protein (pRB) have many features in common. Most strikingly, they contain homologous protein domains that mediate interaction with the oncoproteins of several small DNA tumour viruses, including adenovirus E1A and SV40 large-T antigen. In cells that do not contain these viral oncoproteins, pRB interacts with the cellular transcription factor E2F or a related protein termed DRTF1. E2F associates with a form of pRB that is found primarily in G1 cells. It seems tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
258
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(272 citation statements)
references
References 30 publications
12
258
2
Order By: Relevance
“…A-and B-domains are the most conserved among the three RB proteins and are involved in common functional characteristics (Paggi et al, 1996;Mulligan and Jacks, 1998), the most relevant one being the ability to control the cell cycle by negative modulation of the transition between the G1 and S phases (Goodrich et al, 1991;Zhu et al, 1993;Claudio et al, 1994;Starostik et al, 1996). To perform this task, these 'pocket proteins' utilize mechanisms mostly related to inactivation of transcription factors (Kouzarides, 1995), such as those of the E2F family (Cao et al, 1992;Helin et al, 1992Helin et al, , 1993Shirodkar et al, 1992;Beijersbergen et al, 1994;Hijmans et al, 1995;Sardet et al, 1995;Hurford et al, 1997), that promote the cell entrance into the S phase (Ewen, 1994;Weinberg, 1995;Paggi et al, 1996;Mulligan and Jacks, 1998). Indeed, in addition to the cell cycle, the RB family proteins regulate a wide spectrum of complex biological phenomena, as differentiation, embryonic development, apoptosis and senescence ( (Riley et al, 1994;Sidle et al, 1996;Herwig and Strauss, 1997;Stiegler et al, 1998;Thomas et al, 2003;Liu et al, 2004;Kapic et al, 2006) and references therein).…”
Section: And References Therein)mentioning
confidence: 99%
“…A-and B-domains are the most conserved among the three RB proteins and are involved in common functional characteristics (Paggi et al, 1996;Mulligan and Jacks, 1998), the most relevant one being the ability to control the cell cycle by negative modulation of the transition between the G1 and S phases (Goodrich et al, 1991;Zhu et al, 1993;Claudio et al, 1994;Starostik et al, 1996). To perform this task, these 'pocket proteins' utilize mechanisms mostly related to inactivation of transcription factors (Kouzarides, 1995), such as those of the E2F family (Cao et al, 1992;Helin et al, 1992Helin et al, , 1993Shirodkar et al, 1992;Beijersbergen et al, 1994;Hijmans et al, 1995;Sardet et al, 1995;Hurford et al, 1997), that promote the cell entrance into the S phase (Ewen, 1994;Weinberg, 1995;Paggi et al, 1996;Mulligan and Jacks, 1998). Indeed, in addition to the cell cycle, the RB family proteins regulate a wide spectrum of complex biological phenomena, as differentiation, embryonic development, apoptosis and senescence ( (Riley et al, 1994;Sidle et al, 1996;Herwig and Strauss, 1997;Stiegler et al, 1998;Thomas et al, 2003;Liu et al, 2004;Kapic et al, 2006) and references therein).…”
Section: And References Therein)mentioning
confidence: 99%
“…However, at this time it is not known whether Pura binding to Rb serves any functional role in the cell cycle. In addition, it is not known whether Pura binds to other Rb-like proteins, such as p107 or p130, which may play a role in cell cycle events (Cao et al, 1992;Cobrinik et al, 1993;Ewen et al, 1991;Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993). In human cells both p107 (Devoto et al, 1992) and p130 (Hannon et al, 1993) may be found in complexes with Cyclin A and CDK2, proteins now believed to associated with Pura (Itoh et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Among them are p107 and p130 (for review see Lam and LaThange, 1994;Sherr, 1995). More recently, it has been shown that p107 is phosphorylated by cyclin D/CDK4 and by cyclin E/ CDK2 complexes (Xiao et al, 1996;Lees et al, 1992) and that p107 is able to bind E2F (Starostik et al, 1996;Xiao et al, 1996;Zhu et al, 1995;Zamanian and LaThangue, 1993;Schwarz et al, 1993;Lees et al, 1992;Cao et al, 1992) but also the product of the c-Myc proto-oncogene (Beijersbergen et al, 1994Gu et al, 1994).…”
Section: Introductionmentioning
confidence: 99%